Ectopic Expression of a Self-Incompatibility Module Triggers Growth Arrest and Cell Death in Vegetative Cells - Lin, Zongcheng; Xie, Fei; Triviño, Marina; Karimi, Mansour; Bosch, Maurice; Franklin-Tong, Vernonica E.; Nowack, Moritz K. (Plant physiology (Bethesda), 2020)
Self-incompatibility (SI) is used by many angiosperms to reject self-pollen and avoid inbreeding. In field poppy ( ), SI recognition and rejection of self-pollen is facilitated by a female -determinant, , and a male -determinant, belongs to the cysteine-rich peptide family, whose members activate diverse signaling networks involved in plant growth, defense, and reproduction. and are tightly regulated and expressed solely in pistil and pollen cells, respectively. Interaction of cognate PrsS and PrpS triggers pollen tube growth inhibition and programmed cell death (PCD) of self-pollen. We previously demonstrated functional intergeneric transfer of and to Arabidopsis ( ) pollen and pistil. Here, we show that and , when expressed ectopically, act as a bipartite module to trigger a self-recognition:self-destruct response in Arabidopsis independently of its reproductive context in vegetative cells. The addition of recombinant PrsS to seedling roots expressing the cognate resulted in hallmark features of the SI response, including -specific growth inhibition and PCD of root cells. Moreover, inducible expression of in -expressing seedlings resulted in rapid death of the entire seedling. This demonstrates that, besides specifying SI, the bipartite module can trigger growth arrest and cell death in vegetative cells. Heterologous, ectopic expression of a plant bipartite signaling module in plants has not been shown previously and, by extrapolation, our findings suggest that cysteine-rich peptides diversified for a variety of specialized functions, including the regulation of growth and PCD.